ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAM RETURN ON EQUITY TERHADAP RETURN SAHAM PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2014-2017 - Latifah, Wahyu Ridha; Pratiwi, Permata Dian (Universitas Ahmad Dahlan, 2019)
This research was conducted with the aim to empirically examine the effect of Current Ratio, Debt to Equity Ratio and Return on Equity Against Stock Returns on Real Estate and Property Companies on the Indonesia Stock Exchange. The research period was carried out for 4 (four) years, namely 2014-2017. This type of research is causal research, that is, this study looks for a causal relationship between independent variables and the dependent variable. The population in this study are all Real Estate and Property companies listed on the IDX, wich were 48 Real Estate and Property. The sample in this study was obtained by purposive sampling method that is sampling based on criteria; (1) Registered as an active Real Estate and Property company on the Indonesia Stock Exchange (IDX) in 2014-2017, (2) Companies that publish their annual reports on the IDX, (3) Real Estate and Property Companies that issue CR, DER and ROE for each consecutive period from 2014-2017. Based on these criteria, 36 Real Estate and Property companies were obtained. Hypothesis testing is done by panel data regression analysis, but before testing hypotheses first testing classicalassumptions.The results of hypothesis testing are done partially, namely the t test shows that CR has a positive and insignificant effect on stock returns, DER has a significant negative effect on stock returns and ROE has a significant positive effect on stock returns.